Thermogravimetric characterization of ex situ polymethacrylate (EDMA-co-GMA) monoliths - Acquah, C.; Danquah, Michael; Loo Chin Moy, Charles; Anwar, Mahmood; Ongkudon, C. (Wiley-Blackwell Publishing, 2017)
The thermo-molecular mechanisms associated with free radical synthesis of polymethacrylate monoliths offer an effective pathway to tune their pore characteristics. In this work, thermogravimetric analyses were used for ex situ characterization of polymethacrylate monoliths synthesised from ethylene glycol dimethacrylate (EDMA) and glycidyl methacrylate (GMA). Apparent activation energies of the polymeric monoliths were determined by using Ozawa-Flynn-Wall (OFW) and Kissinger-Akahira-Sunose (KAS) isoconversional methods. The number of degradation stages for the polymers were observed to be as follows: homopolymeric GMA and EDMA (2 degradation stages each) and polymeric EDMA-co-GMA monoliths (3 degradation stages). The relationship between apparent activation energy and extent of conversion showed that the degradation of monoliths is based on a complex multi-step reaction rather than a single reaction model. Kinetic parameters showed that an increase in the composition of EDMA and GMA above 20% significantly enhances the thermal stability of polymeric EDMA-co-GMA monoliths under elevated non-isothermal conditions. E40/G60 and E60/G40 monoliths were identified as the most thermally stable monoliths from the kinetic analyses.